2003
DOI: 10.1046/j.1423-0410.2003.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Red cell transfusion practice following the transfusion requirements in critical care (TRICC) study: prospective observational cohort study in a large UK intensive care unit

Abstract: Clinicians in our centre were conservative, in keeping with recent transfusion guidelines, but deviated from the TRICC protocol by transfusing at haemoglobin concentrations of between 7 and 9 g/dl, rather than below 7 g/dl, and by prescribing 2 unit transfusions. Significant numbers of red-cell units are still used in the critically ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
4
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 17 publications
6
53
4
8
Order By: Relevance
“…[9][10][11][12][13][14] Nonetheless, surveys on transfusion practices have shown that more than 90% of physicians currently transfuse two RBC units simultaneously showing that they have not yet implemented this new transfusion policy. [15][16][17][18] Since data suggest that single-unit transfusions may considerably reduce the total RBC requirements we changed our policy for hospitalized patients without active bleeding from double-to single-unit RBC transfusions. The current study analyzed the effect of the new RBC transfusion policy with regards to the overall RBC requirements and the transfusion efficiency, the adherence to the transfusion policy, as well as safety aspects including bleeding risk and the number of transfused platelets.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Nonetheless, surveys on transfusion practices have shown that more than 90% of physicians currently transfuse two RBC units simultaneously showing that they have not yet implemented this new transfusion policy. [15][16][17][18] Since data suggest that single-unit transfusions may considerably reduce the total RBC requirements we changed our policy for hospitalized patients without active bleeding from double-to single-unit RBC transfusions. The current study analyzed the effect of the new RBC transfusion policy with regards to the overall RBC requirements and the transfusion efficiency, the adherence to the transfusion policy, as well as safety aspects including bleeding risk and the number of transfused platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Acute blood loss following trauma, gas-trointestinal hemorrhage, surgery, among other causes of anemia, are contributing factors for red blood cells transfusion indication in critically ill patients. (4,5) In the last decade, the red blood cells transfusion practice in critically ill patients has been subject to seve ral investigations. Relevant studies in the USA found that the mortality risk increases proportionally to the number of transfused packed red blood cells units, usually above two units.…”
Section: Introductionmentioning
confidence: 99%
“…Bu konuyla ilgili pek çok çalışma bildirilmiştir (14)(15)(16)(17)(18)(19)(20)(21)(22) Bilindiği gibi dokulara oksijen sunumu; Hb konsantrasyonu, Hb değerinin saturasyon yüzdesi ve kalp debisine bağlıdır. Oksijen sunumundaki düşüş; dokudaki oksidatif metabolizmayı engeller ve anaerobik metabolizmaya kaymaya neden olur.…”
Section: Discussionunclassified
“…Oksijen sunumundaki düşüş; dokudaki oksidatif metabolizmayı engeller ve anaerobik metabolizmaya kaymaya neden olur. Aktif kanama olmayan hastalarda Hb 7 g/dL'ye kadar tolere edilebilir (15). Son yıllarda hastanın kliniği ile birlikte dokunun oksijen ihtiyacının karşılanmasının esas alınması gerektiği vurgulanmaktadır (22).…”
Section: Discussionunclassified